Changes in the nutritional composition of okra fruit and seed during early development - Cachero, Tito E.; Belonias, Beatriz S. (Annals of Tropical Research, 2021)
This study investigated the changes in nutrient content of the fruit and seed of Okra or Lady Finger during development and maturation. Okra flowers were tagged at flower opening or anthesis. Sample fruits (technically called capsules) that developed from the tagged flowers were collected at random at 3, 6, 9, 12, 15, 18, 21 and 24 days after anthesis (DAA). The pericarp and seed samples were oven-dried and ground to a powdered form and analyzed for chlorophyll, sugar, starch, crude protein and crude fiber content using standard procedures. Chlorophyll and crude fiber content were strongly positively correlated with fruit age, being lowest in the pericarp of young fruits and highest in older fruits. Sugar, starch and protein content were all negatively correlated with fruit age. They were highest in the pericarp of young 3-day old fruits and steadily decreased with maturity, reaching lowest levels at day 24. In the seeds, protein and starch contents were weakly correlated with fruit maturity. Throughout seed development, sugar remained relatively low while starch and protein content remained high. Based on the results, okra fruits are best harvested as fresh green vegetable at 9 DAA. At this stage, the fruits are succulent, less fibrous and are rich in proteins and carbohydrates. Although much younger fruits also have high nutrient content, they are too small in size, so harvesting them at this stage would not be practical and profitable.